Use of Mass Center to Prove Inequalities - KAMALOV OTABEK ERKIN O‘G‘LI (International Journal on Orange Technologies, 2022)
This paper shows the most commonly used inequalities, in particular the ways to prove the Cauchy inequality using the center of mass. Emphasis is placed on the possibility of proving inequalities by geometric methods.